Contingency Management among Homeless, Out-of-Treatment Men who have Sex with Men - Reback, Cathy J (2010)
Homeless men who have sex with men (MSM) are a particularly vulnerable population with high rates of substance dependence, psychiatric disorders, and HIV prevalence. Most need strong incentives to engage with community-based prevention and treatment programs. Contingency Management (CM) was implemented in a community HIV prevention setting and targeted reduced substance use and increased health-promoting behaviors over a 24-week intervention period. Participants in the CM condition achieved greater reductions in stimulant and alcohol use (χ(2) = 27.36, p<.01) and, in particular, methamphetamine use (χ(2) = 21.78, p<.01), and greater increases in health-promoting behaviors (χ(2) = 37.83, p<.01) during the intervention period than those in the control group. Reductions in substance use were maintained to 9- and 12-month follow-up evaluations. Findings indicate the utility of CM for this high-risk population and the feasibility of implementing the intervention in a community-based HIV prevention program.